2016
DOI: 10.1021/acs.jpcc.6b04862
|View full text |Cite
|
Sign up to set email alerts
|

Atomic and Electronic Structures of a Single Oxygen Molecular Junction with Au, Ag, and Cu Electrodes

Abstract: Fabrication of oxygen molecular junctions was demonstrated for a series of single metal wires of Au, Ag, and Cu using the mechanically controllable break junction method at low temperature (10K). On the basis of conductance measurement, vibrational spectroscopy, and current-voltage (I-V) response of the molecular junctions, we provide experimental evidence that the oxygen can incorporate into the metal wires to form single oxygen molecular junctions. Conductance behavior during elongation process of the molecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…The length of the plateau is reasonable, compared with previously reported small molecules. [ 53,54 ] The corresponding 1D and 2D conductance histograms clearly show that this conductance state is preferable in the breaking process (Figure 1c,d).…”
Section: Resultsmentioning
confidence: 89%
See 3 more Smart Citations
“…The length of the plateau is reasonable, compared with previously reported small molecules. [ 53,54 ] The corresponding 1D and 2D conductance histograms clearly show that this conductance state is preferable in the breaking process (Figure 1c,d).…”
Section: Resultsmentioning
confidence: 89%
“…[57][58][59] Using IETS, we probed the vibrational modes of the molecule inside the nanogap by measuring the conductance change induced by the excitation of the vibrational modes of the molecule by the conduction electrons. [53,[59][60][61] The conductance was enhanced in the dI/dV spectrum, and a prominent peak was observed at 160 meV in an IET spectrum, which represents the main vibrational excitation of the junction (Figure 1e). [53,[59][60][61] This vibrational mode was observed around 120-160 meV (Supporting Information S1, Figure S1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Adsorbed gas atoms or molecules may cause a deviation from integer values in the conductance at room temperature even at ultrahigh vacuum conditions. For this reason, the influence of light gas atoms and molecules on the structural and electronic properties of metallic junctions and point contacts has been widely studied experimentally [18][19][20][21][22][23][24][25][26][27][28] and theoretically [29][30][31][32][33][34]. For instance, using the MCBJ technique it has been shown that oxygen atoms can be incorporated in noble metal (Au, Ag, Cu) atomic chains, leading to a considerable reduction in conductance for Ag and Cu chains and retaining the conductance near one quantum unit (1g 0 = 2e 2 /h) for Au atomic chains [23,25].…”
Section: Introductionmentioning
confidence: 99%